(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Consumption of fruits and vegetables in Indonesia is still lacking (5%), even though fruits and vegetables play a role in maintaining the condition of blood pressure, blood sugar and cholesterol levels to prevent non infectious diseases. One way to increase public awareness to consume fruits and vegetables is through health education. Health education through audiovisual media is considered important because it displays elements of moving images and sounds that stimulate more senses. This study aims to determine the effectiveness of audiovisual health education media to increase knowledge, attitudes, and behavior of adolescents in the consumption of vegetables and fruit every day. This research uses quasi experiment method. The sample of this research is grade 6 students of Menteng State 5, Elementary School in Palangka Raya. The results showed an increase in the proportion of knowledge and good attitude after the intervention period (p-value: 0.008 and 0.002). There is no significant relationship between sex with students’ knowledge and attitudes towards vegetable and fruit consumption (p-value: 1.0 and 0.71).